(3CKQ GdEOGQI GdEdcJQhfjI aj EOGQI GdeQGab GdYGeI (B:s (3OQGSI ebGQfI (B/s - (3GdCMHGHj, fHQGS eMeO LGSes ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdLGeYI GdLOjOI,s, 2018)
(3jJfGhd cJGH (B((3CKQ GdEOGQI GdEdcJQhfjI aj EOGQI GdeQGab GdYGeI(B: (3OQGSI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3fHQGS eMeO LGSe GdCMHGHj(B) (3aj MhGdj (B(224) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdEfJQfJ aj GdEOGQI GdYGeI(B-(3GdeQGab GdYGeI(B-(3EOGQI(B-(3eYGdLI HjGfGJ(B-(3bhGfjf hJTQjYGJ(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdeHMK GdJegjOj (B: (3eGgjI GdEOGQI GdEdcJQhfjI, GdaUd GdChd (B: (3OhQ GdEOGQI GdEdcJQhfjI aj EOGQI GdeQab GdYGe, GdaUd GdKGfj (B: (3OhQ GdEOGQI GdEdcJQhfjI aj CYeGd ehXaj GdeQab(B.s
(3GdeMJhjGJ (B: (3GdeHMK GdJegjOj (B: (3eGgjI GdEOGQI GdEdcJQhfjI, GdeWdH GdChd (B: (3fTCI heaghe GdEOGQI GdEdcJQhfjI hYfGUQgG (B...-(3GdaUd GdChd (B: (3OhQ GdEOGQI GdEdcJQhfjI aj EOGQI GdeQab GdYGe, GdeHMK GdChd (B: (3OhQ GdEOGQI GdEdcJQhfjI aj GdeHGOF GdJj JMce SjQ GdeQab GdYGe (B...-(3GdaUd GdKGfj (B: (3OhQ GdEOGQI GdEdcJQhfjI aj CYeGd ehXaj GdeQab GdYGe, GdeHMK GdChd (B: (3JjSjQ ELQGAGJ GdCYeGd GdeGOjI, hGdGQJbGA HcaGAI COGFgG (B...-(3hehVhYGJ CNQi(B.s
(3HHdjhLQGajI (B: (3UaMI (B196-218.s
(3jTJed Ydi edNU HGddZI GdEfLdjRjI(B.s
Keywords: (3GdEfJQfJ aj GdEOGQI GdYGeIs -- (3bhGfjf hJTQjYGJs; (3GdeQGab GdYGeIs -- (3EOGQIs -- (3eYGdLI HjGfGJs